A Comparative Study of Congo Red Textile Dye Photodegradation Using ZnO Al and ZnO Al+Mn Nanoparticles - Krisandi, Aprilion; Harsono, Heru; Yudasari, Nurfina (Trends in Sciences, 2024)
Photodegradation of Congo Red textile dye was successfully carried out using ZnO Al and ZnO Al+Mn nanoparticles synthesized using the bottom-up coprecipitation method. Powder X-ray diffraction provides information that Al and Mn doping successfully inserted in the host crystal structure while maintaining the Hexagonal Wurtzite crystal structure. However, a shift in the diffraction peak caused by the lattice distance changes with the addition of doping. FE-SEM EDS provides information that both nanoparticles are nonuniform sphere-like due to the addition of dopping, and each dopping is detected through EDS spectra. There is a decrease in the gap energy in each sample. ZnO Al nanoparticles have a gap energy of 3.29 eV, and ZnO Al+Mn nanoparticles have a gap energy of 3.28 eV. However, the decrease in the gap energy is not directly related to the percentage and kinetic rate of Congo Red photodegradation. Adding 5 mg of ZnO Al Nanoparticles powder could degrade Congo Red up to 97.9 % within 120 min using UV A radiation or 0.03504/min. At the same time, adding ZnO Al+Mn Nanoparticles powder with the same parameters could only degrade 67.6 % or 0.00759/min. HIGHLIGHTS Energy Bandgap Modification of ZnO Nanoparticles The incorporation of Al single dopants and Al, Mn co-dopants into ZnO nanoparticles synthesized via a bottom-up coprecipitation method significantly alters the energy bandgap. Al single doping resulted in a bandgap of 3.29 eV, while Al, Mn double doping yielded a bandgap of 3.28 eV. Enhanced Photocatalytic Activity of Al-Doped ZnO Al-doped ZnO nanoparticles exhibited superior photocatalytic activity toward the degradation of Congo Red textile dye. With a photodegradation rate constant of 0.03504 min⁻¹, these nanoparticles achieved 97.9 % degradation of Congo Red within 120 minutes. Comparative Photocatalytic Performance of Al, Mn Co-Doped ZnO While Al, Mn co-doped ZnO nanoparticles were synthesized using the same method, their photocatalytic performance for Congo Red degradation was notably lower than that of Al-doped ZnO. The calculated photodegradation rate constant was 0.00759 min⁻¹, resulting in 67.6 % degradation within the same timeframe. GRAPHICAL ABSTRACT